Fundamentals and technology of combustion - El-Mahallawy, F. M.; Habik, Saad El-Din. (Amsterdam ; Boston : Elsevier, 2002)
Fundamentals and Technology of Combustion contains brief descriptions of combustion fundamental processes, followed by an extensive survey of the combustion research technology. It also includes mathematical combustion modeling of the processes covering mainly premixed and diffusion flames, where many chemical and physical processes compete in complex ways, for both laminar and turbulent flows. The combustion chemistry models that validate experimental data for different fuels are sufficiently accurate to allow confident predictions of the flame characteristics. This illustrates a unique bridge between combustion fundamentals and combustion technology, which provides a valuable technical reference for many engineers and scientists. Moreover, the book gives the reader sufficient background of basic engineering sciences such as chemistry, thermodynamics, heat transfer and fluid mechanics. The combustion research and mathematical models fit between small-scale laboratory burner flames, and large-scale industrial boilers, furnaces and combustion chambers. The materials have been collected from previous relevant research and some selected papers of the authors and co-workers, which have been presented mainly in different refereed journals, international conferences and symposia, thus providing a comprehensive collection. Furthermore, the book includes some of the many recent general correlations for the characteristics of laminar, turbulent, premixed and diffusion flames in an easily usable form. The authors believe that further progress in optimizing combustion performance and reducing polluting emissions can only be treated through understanding of combustion chemistry.
Combustion fundamentals. Laminar premixed flames. Turbulent premixed and diffusion flames. Characteristics of turbulent confined diffusion flames. Combustion, heat transfer, and emission in boilers and furnaces.
Includes bibliographical references (p. 779-834) and index.
Keywords: Combustion engineering; Electronic books